Detection of Entomological Origin of Honey Sold in Indonesia Based on 16S rRNA Gene Analysis - Indahsari, Anita Nur; Purwanto, Hari (Universitas Gadjah Mada, 2024)
Honey is known for its various benefits for health, cosmetic ingredients, and other industrial materials. Especially, during the Covid-19 pandemic, many people consume honey to maintain body endurance. In Indonesia, the honey produced is dominated by Apis mellifera honey. With a cheaper price and a larger quantity, A. mellifera honey is often offered as forest honey or stingless bee honey to get more profit. Therefore, this study aims to determine the entomological origin of honey claimed as forest honey and stingless bee honey sold in the Indonesian market using the detection of 16S rRNA gene amplicon. This study tested 30 samples of forest honey and 30 samples of stingless bee honey. DNA that has been isolated from honey samples was amplified by PCR using 16S rRNA primers. The results from the sequence analysis showed that nine of honey samples were identified as honey fraud. Two samples were confirmed as falsification of the origin of honey-producing bees and four honey samples were confirmed as honey mislabelling. From this study it can be concluded that, it is possible to determine the entomological origin of honey molecularly by sequencing the 16S rRNA gene. Therefore, this method can be used to identify honey fraud that may occur on the market.